Beyond LDL-c: The importance of serum oxidized LDL in predicting risk for type 2 diabetes in the middle-aged Asian Indians. Issue 1 (January 2019) - Banerjee, Joyita; Mishra, Neetu; Damle, Gauri; Dhas, Yogita
Abstract: Aims: Oxidized low-density lipoprotein (OxLDL) as the residual lipid plays a crucial role in cardiovascular complications and type 2 diabetes. This study aimed to evaluate the relationship of OxLDL with the conventional risk markers and to find the association of OxLDL with the risk of development of type 2 diabetes in middle-aged (30–50 years) Asian Indians. Materials and methods: A total of 78 type 2 diabetes patients and 78 age-matched controls were recruited. The serum OxLDL concentration was assessed by enzyme-linked immunosorbent assay (ELISA). Other anthropometric and biochemical measures were also carried out. Multiple logistic regression was used to determine the association of OxLDL and OxLDL to non-oxidized lipoproteins with the occurrence of type 2 diabetes. Results: OxLDL was significantly higher in type 2 diabetes cases than controls (p < 0.001) even though there was no significant difference in LDL cholesterol (LDL-c) between type 2 diabetes patients and controls. OxLDL correlated significantly with fasting plasma glucose (FPG) and insulin resistance (HOMA-IR). OxLDL did not show any significant correlation with LDL-c. Multiple logistic regression showed a significant association of OxLDL, OxLDL/LDL-c and OxLDL/HDL-c with type 2 diabetes (p < 0.001). LDL-c showed no association with type 2 diabetes. ROC-AUC curve analyses showed OxLDL/HDL-c to have highest discriminatory power for type 2 diabetes (AUC: 0.710 with 95% CI: 0.629–0.791, p < 0.001). Conclusion: Our findings highlight the possibly more attention has to be given to OxLDL for managing lipids and diabetes progression as well as reducing cardiac risk in middle-aged type 2 diabetes patients. Graphical abstract: Highlights: A significant association of OxLDL with type 2 diabetes was observed in middle-aged Asian Indians. OxLDL was found to have higher discriminatory power to predict risk of type 2 diabetes than LDL-c. OxLDL as residual lipid needs more attention to minimize the risk of type 2 diabetes.